1998
DOI: 10.1136/sti.74.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in patients attending a genitourinary medicine clinic: risk factors and vaccine coverage

Abstract: Background:The hepatitis B virus (HBV) immunisation policy in the United Kingdom includes oVering vaccine selectively to those at risk by sexual contact. Among genitourinary medicine (GUM) clinic attenders, homosexual men are oVered vaccine, but estimates of the vaccine uptake are required to monitor policy and estimate the possible impact on transmission; heterosexuals are not routinely oVered vaccine, but this policy might change if the prevalence was found to be high. Objective: To determine the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Both observations suggest that the transmission rate through male homosexual contact is decreasing, and contrasts with the current increase in high risk sexual behaviour and outbreaks of other sexually transmitted infections among MSM (PHLS, 2002). The decreased incidence of HBV in MSM is likely to be attributable to increased HBV vaccine coverage in this group, which is consistent with information from surveys among MSM attending GUM clinics (Gilson et al, 1998). Coverage among MSM is being improved by offering HBV vaccine to all MSM attending GUM clinics, with central purchase and supply of vaccine, and clear coverage targets being set (Department of Health, 2001).…”
Section: Homosexual Transmissionmentioning
confidence: 74%
“…Both observations suggest that the transmission rate through male homosexual contact is decreasing, and contrasts with the current increase in high risk sexual behaviour and outbreaks of other sexually transmitted infections among MSM (PHLS, 2002). The decreased incidence of HBV in MSM is likely to be attributable to increased HBV vaccine coverage in this group, which is consistent with information from surveys among MSM attending GUM clinics (Gilson et al, 1998). Coverage among MSM is being improved by offering HBV vaccine to all MSM attending GUM clinics, with central purchase and supply of vaccine, and clear coverage targets being set (Department of Health, 2001).…”
Section: Homosexual Transmissionmentioning
confidence: 74%
“…Although the heterosexual transmission of HBV is related as more frequently than homosexual transmission (Alter 1990, Duarte 1992, recent studies in STD clinics (Stroffolini et al 1997, Gilson et al 1998 showed the opposite. In answering about homosexual behaviour, 3.6% of the 2000).…”
Section: Discussionmentioning
confidence: 94%
“…In areas of low endemicity the sexual contact is the major route of transmission. Extensive studies regarding HBV sexual transmission have been conducted in low HBV endemic countries (Struve et al 1993, Gilson et al 1998. Heterosexuals who have unsafe sex with multiple partners and homo/bisexual men are the high-risk groups for sexual transmission (Margolis et al 1991).…”
mentioning
confidence: 99%
“…On the one hand, low attendance rates in genitourinary medicine (GUM) clinics and poor vaccination coverage of IDUs reported in several papers have been used to call into question the feasibility of selective vaccination [44][45][46][47], and to raise the issue of whether heterosexuals who attend GUM clinics, should also be vaccinated [48]. On the other hand, the observed reduction in the incidence of acute HBV in very low and low endemic countries before the era of universal vaccination has been interpreted indicating that selective vaccination strategies could be sufficient in these countries [49].…”
Section: Countries Of 6ery Low Endemicitymentioning
confidence: 99%